Long‐Term Effects of Severe Burn Injury on Bone Turnover and Microarchitecture. (9th November 2017) - Muschitz, Gabriela Katharina; Schwabegger, Elisabeth; Fochtmann, Alexandra; Baierl, Andreas; Kocijan, Roland; Haschka, Judith; Gruther, Wolfgang; Schanda, Jakob E; Resch, Heinrich; Rath, Thomas; Pietschmann, Peter; Muschitz, Christian
ABSTRACT: Severe burn injury triggers massive alterations in stress hormone levels with a dose‐dependent hypermetabolic status including increased bone resorption. This study evaluated bone microarchitecture measured by noninvasive high‐resolution peripheral quantitative computed tomography (HR‐pQCT). Changes of serum bone turnover markers (BTM) as well as regulators of bone signaling pathways involved in skeletal health were assessed. Standardized effect sizes as a quantitative measure regarding the impact of serum changes and the prediction of these changes on bone microarchitecture were investigated. In total, 32 male patients with a severe burn injury (median total body surface area [TBSA], 40.5%; median age 40.5 years) and 28 matched male controls (median age 38.3 years) over a period of 24 months were included. In patients who had sustained a thermal injury, trabecular and cortical bone microstructure showed a continuous decline, whereas cortical porosity (Ct.Po) and pore volume increased. Initially, elevated levels of BTM and C‐reactive protein (CRP) continuously decreased over time but remained elevated. In contrast, levels of soluble receptor activator of NF‐κB ligand (sRANKL) increased over time. Osteocalcin, bone‐specific alkaline phosphatase (BALP), intact N‐terminal type 1 procollagen propeptide (P1NP), and cross‐linked C‐telopeptide (CTX) acutely reflected the increase of Ct.Po at the radius (R 2 = 0.41), followed by the reduction of trabecular thickness at the tibia (R 2 = 0.28). In adult male patients, early and sustained changes of markers of bone resorption, formation and regulators of bone signaling pathways, prolonged inflammatory cytokine activities in conjunction with muscle catabolism, and vitamin D insufficiency were observed. These alterations are directly linked to a prolonged deterioration of bone microstructure. The probably increased risk of fragility fractures should be of clinical concern and subject to future interventional studies with bone‐protective agents. © 2017 American Society for Bone and Mineral Research